2004
DOI: 10.1128/aem.70.6.3541-3551.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Rhizosphere Microbial Communities Associated with Healthy and Diseased Black Spruce ( Picea mariana ) Seedlings Grown in a Nursery

Abstract: Bacterial and fungal populations associated with the rhizosphere of healthy black spruce (Picea mariana) seedlings and seedlings with symptoms of root rot were characterized by cloned rRNA gene sequence analysis. Triplicate bacterial and fungal rRNA gene libraries were constructed, and 600 clones were analyzed by amplified ribosomal DNA restriction analysis and grouped into operational taxonomical units (OTUs). A total of 84 different bacterial and 31 different fungal OTUs were obtained and sequenced. Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 38 publications
3
56
2
1
Order By: Relevance
“…In accordance with previous studies, we also observed shifts in the structure of bacterial community in diseased plants, but there were large differences in the extent of these changes. Similar to the results of this study, Filion et al (2004) have reported negative effects of root rot disease on the stability of the rhizosphere bacterial community of black spruce (Picea mariana) seedlings. In contrast, few studies have reported increase in bacterial diversity in pathogen-infested plants (Yang et al, 2001;Reiter et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In accordance with previous studies, we also observed shifts in the structure of bacterial community in diseased plants, but there were large differences in the extent of these changes. Similar to the results of this study, Filion et al (2004) have reported negative effects of root rot disease on the stability of the rhizosphere bacterial community of black spruce (Picea mariana) seedlings. In contrast, few studies have reported increase in bacterial diversity in pathogen-infested plants (Yang et al, 2001;Reiter et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, few studies have reported increase in bacterial diversity in pathogen-infested plants (Yang et al, 2001;Reiter et al, 2002). Interestingly, shifts in the structure of fungal community in response to pathogen infection have also been observed (Filion et al, 2004;Vujanovic et al, 2007). We postulate that the nature of fluctuations in the structure and function of plant-associated microbial community would be differentially determined by the virulence mechanism(s) of the pathogen and the response of host plant-to-pathogen infection.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Selection for Proteobacteria in the rhizosphere of Trifolium repens and Lolium perenne has been attributed to the nutrient-rich conditions of the rhizosphere (31), and similar results have been obtained in other plant systems, such as maize (38), soybean (52), and grasslands (42). However, in other woody species, such as chestnut trees (28) and black spruce (13), Acidobacteria have been shown to dominate rhizosphere systems. In our study, Proteobacteria were only slightly more prevalent (43% of sequences) than the Acidobacteria (38%), which may indicate a level intermediate between the copiotrophic and oligotrophic conditions thought to characterize the preferred habitats of these groups.…”
Section: Vol 77 2011 Bacterial and Fungal Communities Of Populus Desupporting
confidence: 48%
“…Many studies on the microbial community structure of the rhizosphere and rhizoplane of terrestrial plants have been conducted using cultivation-based and cultivation-independent methods (12,18,21,22,31,40). These studies have shown that terrestrial plants harbor unique and diverse microbial communities in their rhizoplane probably due to the specific environments formed by the surface structure and exudates released from the roots.…”
mentioning
confidence: 99%